DISEASES OF THE ORAL CAVITY IN PROFESSIONAL ATHLETES ENGAGED IN VARIOUS SPORTS - Hajiyev, D.G. (World of Medicine and Biology, 2022)
475 athletes, representatives of the Olympic reserve in game and power sports, were examined during intensive training of the preparatory period of the training cycle (75 % – boys and 25 % – girls) aged 18 to 21 years. The article presents the data of scientific studies of the dental status of 200 athletes divided into groups depending on the type of sport: game types (volleyball, handball), wrestling, swimming, gymnastics, boxing. The control group consisted of 40 students of the Azerbaijan Medical University who do not have a somatic burden and are engaged in amateur sports. The prevalence of the main dental diseases was studied: caries, inflammatory periodontal diseases, using the methods and criteria proposed by WHO – the index of need for treatment of periodontal diseases, CPITN, 1980 and the CPI index. The hygienic condition of the oral cavity was determined by the OHI-S index (JC Green, JR Vermillion, 1963), gum bleeding according to Muhlemann-Cowell (SB–Index), the condition of periodontal tissues according to the PMA index (Massler, Schour (1949) modified by Parma (1960)). Inflammatory periodontal diseases are more often diagnosed in sports such as wrestling, gymnastics. The highest frequency of diagnosis of bleeding is noted in athletes – wrestlers and boxers. The lowest level of bleeding was found in representatives of game sports. When assessing the prevalence of carious disease in the wrestling and swimming group, equal values are determined – 60.0±7.75 %.